(untitled) (Research, Society and Development, 2021)
Objective: To analyze the conceptual dimension of social representations of neglected diseases for health professionals. Method: This is a study with a qualitative approach, supported by the Theory of Social Representations, developed in primary and secondary care units in a municipality in the interior of Bahia, Brazil, with health professionals. Data were collected through in-depth interviews and submitted to lexical analysis using the IRAMUTEQ software. Results: Health professionals were divided into three categories: nurses (09); nursing technicians (09) and doctors (09); mostly 85.5% were female, aged between 26 and 69 years. The study focuses on the discussion of axis 1 called Concepts, Knowledge and Contexts of Neglected Diseases. Discussion: The content of health professionals’ social representations about neglected diseases constitutes a conceptual dimension that encompassed concepts, characteristics and causes of these diseases, supporting the idea of contagion and transmissibility of these diseases, strengthening neglect, prejudice and lack of interest since the individual to the collective rooting the culture of neglect the populations with greater social vulnerability. Conclusion: The conceptual dimension of the social representations of health professionals about neglected diseases provided the construction of their definitions and causes closely linked to social conditions, individual perceptions and government practices that together make up a structured base on the perpetuation of these diseases, including social weaknesses, such as the lack of basic knowledge of healthy habits, social neglect, both of the health team and managers.